Interaction of Coxiella burnetii Strains of Different Sources and Genotypes with Bovine and Human Monocyte-Derived Macrophages - Sobotta, Katharina; Hillarius, Kirstin; Jiménez, Pablo H.; Kerner, Katharina; Heydel, Carsten; Menge, Christian (Frontiers in Cellular and Infection Microbiology, 2018)
Most human Q fever infections originate from small ruminants. By contrast, highly prevalent shedding of Coxiella (C.) burnetii by bovine milk rarely results in human disease. We hypothesized that primary bovine and human monocyte-derived macrophages (MDM) represent a suitable in vitro model for the identification of strain-specific virulence properties at the cellular level. Twelve different C. burnetii strains were selected to represent different host species and multiple loci variable number of tandem repeat analysis (MLVA) genotypes. Infection efficiency and replication of C. burnetii were monitored by cell culture re-titration and qPCR. Expression of immunoregulatory factors after MDM infection was measured by qRT-PCR and flow cytometry. Invasion, replication and MDM response differed between C. burnetii strains but not between MDMs of the two hosts. Strains isolated from ruminants were less well internalized than isolates from humans and rodents. Internalization of MLVA group I strains was lower compared to other genogroups. Replication efficacy of C. burnetii in MDM ranged from low (MLVA group III) to high (MLVA group IV). Infected human and bovine MDM responded with a principal up-regulation of pro-inflammatory cytokines such as IL-1β, IL-12 and TNF-α. However, MLVA group IV strains induced a pronounced host response whereas infection with group I strains resulted in a milder response. C. burnetii infection marginally affected polarization of MDM. Only one C. burnetii strain of MLVA group IV caused a substantial up-regulation of activation markers (CD40, CD80) on the surface of bovine and human MDM. The study showed that replication of C. burnetii in MDM and the subsequent host cell response is genotype-specific rather than being determined by the host species pointing to a clear distinction in C. burnetii virulence between the genetic groups.